Study on seismic failure probability of high earth-rock dam considering dam body deformation and slope stability. Issue 9 (4th July 2022) - Li, Yanlong; Tang, Wang; Wen, Lifeng; Wang, Jing
Abstract: The reliability analysis is one of the main methods for the quantitative analysis of the safety in the geotechnical engineering. This method can provide the failure probability with a clear physical meaning. Due to the complex structure of high earth-rock dams and the non-linear characteristics of the material properties, it is very difficult to perform the reliability analysis on such large nonlinear structures. Currently, there are few studies on the reliability analysis of high earth-rock dams that consider the earthquakes, the dam body deformation and the dam slope stability at the same time. In this paper, the dam cracks generated by the earthquakes are used as the criteria for the dam body seismic deformation evaluation, and the inclination method is adopted for the dam body seismic deformation analysis. The simplified Bishop method combined with the ratio of the safety margin method is used to analyze the dam slope stability. In order to consider the soil material properties, the thickness of the compressible soil layer and the uncertainty of the earthquakes, a seismic failure probability analysis method for evaluating the seismic danger of high earth-rock dams considering the dam body deformation and the dam slope stability is established based on the reliability theory. Taking a concrete face rockfill dam as an example, the method is used to analyze the seismic failure probability of the dam during the design reference period. It provides the reference for the seismic design and the risk analysis, and establishes the risk level of high earth-rock dams.